Cometary ion instabilities in the solar wind. (15th December 2015) - Matteini, L.; Schwartz, S.J.; Hellinger, P.
Abstract: We review some of the processes that characterize the interaction of the solar wind with newborn cometary ions. Instabilities generated by the typical ring-beam velocity-space configuration of the pick-up ions in the solar wind frame are studied by means of one- and two-dimensional hybrid numerical simulations. In agreement with previous studies, we find that instabilities generated by the cometary ions play an important role in shaping the properties of the plasma. The resulting ion distributions are in good agreement with observations, showing the presence of energy shells in velocity space. Bi-spherical shells for the heavy oxygen ions are also observed in the late phase of the simulations. Moreover, we also investigate some new aspects of the dynamics, such as the generation of turbulent cascade from the initial spectra of unstable waves, and the related heating and back reaction of the solar wind plasma. We also consider the case of initial non-gyrotropic pick-up ion distributions, and we focus on the polarization of the associated waves, suggesting that linear polarization can be a signature of this configuration, possibly observed by the Rosetta spacecraft in orbit around comet 67P/CG. Abstract : Highlights: Simulations of cometary pick-up ion instabilities and good agreement with data. Feedback on the solar wind proton energetics is considered. Non-gyrotropic ion distributions lead to unstable linearly polarized fluctuations.